Black Bodies, Virility and Power in Medical Literature in a Colonial Context - (:unkn) unknown (My University, 2019)
The black man’s body is subject to two types of representations in the French medical literature from the nineteenth century to the middle of the twentieth century. Descriptions of black men often contributed to emphasizing the virility of white men. Indeed, African men were described as physically and intellectually effeminate, similar to women and children, inferior and lacking authority. This inferiority was used to legitimize the colonization of Africa by men of the French nation, who were presented as manly and powerful, and thus able to protect the African population. Parallel to this representation, another stereotype emerged at the turn of the nineteenth and twentieth century with the development of the naturist doctrine and colonization, this time foregrounding the hyper-virility of black men. The representation of his robust, resistant, strong and muscular body, was contrasted to the weakened body of white men, at a time when, in the colonies, white men suffered from the climate and tropical diseases and, in France, the defeat of 1870 led to rising fear about the “decline of the race”. So, the definition of black man’s masculinity evolves during the nineteenth century and the beginnings of the twentieth century according to the political context and the sexual and social norms prevailing in France.
Keywords: African Research